Numerical and experimental study of aircraft structural health. (March 2020) - Martins, T.; Infante, V.; Sousa, L.; Fonseca, A.; Antunes, P.J.; Moura, A.M.; Serrano, B.
Highlights: The service load spectrum and the strain response of the structure are measured by using accelerometers and strain gauges. Finite element models of critical components are used to define the critical locations for the sensors. The fleet operation is analysed to calculate the fatigue damage of the aircraft. The service measurements are analysed using a the structural health monitoring platform. Abstract: The purpose of this work is to monitor the structural health of the Portuguese Air Force (PoAF) EPSILON TB30 fleet by measuring the dynamic behaviour of aircraft's critical components towards the optimization of maintenance programme scheduling. The mission load spectrum and the structural response are simultaneously measured using a combination of accelerometers and strain-gauges, enabling the calculation of individual transference functions for each critical component monitored. The EPSILON TB30 fleet was divided into two different types of aircrafts: a) IMA-Highly Instrumented Aircrafts which are able to capture vertical accelerations and strain at critical locations and b) LIA-Less Instrumented Aircrafts that make use of the transference functions for mapping the captured acceleration data to stress at pre-selected structural hotspots. The fleet operation is continuously analysed to calculate the fatigue damage of each component and predict the operation limit for each aircraft. In this context, finite element models of critical components are used to define the critical locations of sensors used for monitoring stress in those locations. The maximum principal stress zones of the 2nd bulkhead beam was obtained and are consistent with the manufacturer's reports that place fatigue crack initiation near the bottom filleted joint of the innermost rib, during real scale fatigue test. Mission is analysed using the structural health monitoring platform PRODDIA™ Aero which uses time and frequency-based fatigue models to predict the structural health of the entire fleet.